Linear ubiquitin chain assembly complex coordinates late thymic T-cell differentiation and regulatory T-cell homeostasis - Charis E. Teh (Nature Portfolio, 2016)
LUBAC is a ubiquitin ligase complex of HOIL-1, HOIP and SHARPIN important for signal transduction of a range of stimuli. Here the authors define the function of all three LUBAC components in T cell development and homeostasis.